A study on how to enhance the well-being of young professionals confronting internal overcompetition in China: Prospect of reducing the stress of Nei Juan - Chen Mingze; Yasuyuki Yamaoka; Sitsada Sartamorn; Hiroko Oe (Health Economics and Management Review)
In today’s China, internal overcompetition is a serious problem for people’s mental and physical health. It provokes stress and fatigue, physical and mental exhaustion; reduces educational qualifications; makes it difficult to find a job; leads to irregular patterns of overtime work (e.g., “996” and “007”). In China, the scale of this problem is so great that it is considered a separate concept (Nei Juan). Since 2021, it has been a subject to regulation by the government. When considering this problem, it is important to understand its dual nature and strike a balance. On the one hand, sustainable competition stimulates innovation and technological progress, nurtures talent, strengthens the nation’s qualification potential, contributing to China’s emergence as a global economic centre. On the other hand, it leads to effort inflation, which can deprive employees of motivation and lead to their leaving abroad. With this in mind, the article formulates eight research hypotheses and builds two mathematical models. The first model considers this dual nature of internal overcompetition through a complex system of interdependent relationships that mediate its impact on human life as a stimulant (promoting self-discipline, resilience, increased self-esteem and self-confidence) and an inhibitor (relentless race for achievement, loss of joy in life). The second model also takes into account the role of family and encouragement from the immediate environment to reduce stress as a mediating variable. The study was based on a survey of 280 working adults in China aged 20 to 40 with less than six years of work experience. Answers to 14 questions were rated on the 5-point Likert scale. The data were analysed via IBM SPSS Version 26 and SPSS AMOS Version 26. The following statistical methods were used in the study: descriptive statistics, correlation analysis, factor analysis, and structural modelling. Data reliability was confirmed using the Cronbach’s alpha coefficient. The sample adequacy was confirmed using the Kaiser-Meyer-Olkin criterion. Convergent and discriminant validity was also confirmed. Four of eight research hypotheses were proven. Young professionals who previously faced competition in high school and university now face competition in society. To cope with this stress, they seek support from their families and effective organisational support; they find meaning in overcoming competition while making efforts. The study results form the basis for the development of support measures aimed at overcoming internal overcompetition. They provide valuable information on how to navigate the difficult conditions faced by the younger generation.